Household sorting in an ancient setting - Abhimanyu Gupta; Jonathan Halket (Centre for Microdata Methods and Practice (cemmap), 2021)
We use archaeological data from ancient settlements of three different historical eras on a Greek island to construct novel measures of consumption. Using these, we show that luxury good consumption was higher closer to the center of nucleated settlements but shows no such pattern in a placebo settlement. We build a monocentric agglomeration model with heterogeneous households, luxury goods and endogenous labor choices that is consistent with the rich living closer to the center and consuming more luxuries. This result holds when intra-settlement transportation costs within the model are predominately time costs, as they mostly were in ancient history.
Keywords: N93; R21; 330; Sorting; Luxury goods; Archaeology; Urban